Assessment of the SRC Inhibition Role in the Efficacy of Breast Cancer Radiotherapy - Shahrokh, Shabnam; Mansouri, Vahid; Razzaghi, Zahra (Journal of Lasers in Medical Sciences, 2019)
Introduction: Exposure to the artificial light at night (LAN) effect human health and causes several functional modification in body. Obesity, diabetes, and hormonal changes are reported after LAN in humans. Aim of this study is highlighting critical features of gene expression changes in liver of rats which are received autonomic nervous system. Methods: Up-regulated proteins of irradiated MDA-MB-231 breast cancer cells by a single and fractioned 10 Gray (Gy) 137Cs γ-radiation were analyzed by ptotein-protein interaction (PPI) network analysis by Cytoscape software via STRING database. The network were analyzed by using Network analyzer to characterized the central genes. Action map was mapped for the queried genes and the added neighbors. via CluePedia-STRING ACTIONS-v10.5- 20.11.2017. Results: The 14 differentially expressed proteins (DEPs) plus 10 neighbors were interacted to construct a network. Among the 14 queried DEPs FN1, CSPG4, LRP1, GSN, RTN4, and CTSD were highlighted as a complex set in analysis. Analysis revealed that SRC as an added neighbor were activated by the critical DEPs. Activation of the other oncogene as like AKT1 also were determined. Conclusion: The results indicate that the inhibition of SRC activity or the inhibition of its activators is a useful function of breast cancer RT.